Brillouin fibre laser with 20 m-long photonic crystal fibre - Harun, Sulaiman Wadi; Aziz, Siti Narimah; Tamchek, Nizam; Shahabuddin, Nurul Shahrizan; Ahmad, Harith (Institution of Engineering and Technology, 2008)
Brillouin fibre laser is demonstrated using a very short length of photonic crystal fibre (PCF). A simple ring resonator is used in the experiment which consists of a 20m long highly nonlinear PCF and 49cm long Bismuth-based erbium-doped fibre (Bi-EDF). The proposed Brillouin laser is able to generate up to 3 Stokes and 3 anti-Stokes lines in the 1560nm region at a channel spacing of 0.09nm.